The Safety, Efficacy and Therapeutic Potential of Histone Deacetylase Inhibitors with Special Reference to Panobinostat in Gastrointestinal Tumors: A Review of Preclinical and Clinical Studies - Singh, Avineesh; Patel, Preeti; Jageshwar; Patel, Vijay K.; Jain, Deepak Kumar; Kamal, M.; Rajak, Harish (Current Cancer Drug Targets, 2018)
Histone deacetylase inhibitors (HDACi) have been demonstrated as an emerging class of anticancer drugs involved in regulation of gene expression and chromatin remodeling thus indicating valid targets for different types of cancer therapeutics. The pan-deacetylase inhibitor panobinostat (Farydac®, LBH589) is developed by Novartis Pharmaceuticals and a newly US FDA approved drug for the multiple myeloma. It is under clinical investigation for a range of hematological and solid tumors worldwide in both oral and intravenous formulations. Panobinostat inhibits tumor cell growth by interacting with acetylation of histones and nonhistone proteins as well as various apoptotic, autophagy-mediated targets and various tumorigenesis pathways involved in the development of cancer. The current article summarizes the status of panobinostat in gastrointestinal cancers. Preclinical and clinical data suggest that panobinostat has potential inhibitory activity in hepatocellular, pancreatic, colorectal, gastric and gastrointestinal stromal tumors. Clinical evaluations of panobinostat are currently underway. Herein, we have also reviewed the rationale behind the combination therapy under the trials and possible future prospective for the treatment of GI tumors.
Keywords: HDACi